An Econometric Analysis of the Links Between Income Inequality and Economic Growth - Hailu, Yohannes G.; Gebremedhin, Tesfa G.; Jackson, Randall W. (Journal of Income Distribution®, 2009)
This study investigates temporal demographic changes and incomeinequalities, and more importantly the relationship between income inequalityand economic growth inWest Virginia. Departing from earlierstudies, a regional growth model is utilized and empirically tested usingcounty level West Virginia data (1990-2000). Results suggest thatper-capita income change is positively related to population and employmentchanges but negatively related to income inequality. Thisempirical evidence indicates that higher income inequality can potentiallyhinder economic growth.